Effect of Education on Promoting Preventive Behaviors of Premenstrual Syndrome in Female Adolecents: Health Belief Model Application - Mania Khalilipour; Rahman Panahi (Hamadan University of Medical Sciences, 2017)
Background and Objective: Premenstrual syndrome reduces the quality of life as well as social and academic performance in adolecents and young women. Given the importance of the preservation of the female adolecents' health status, this study aimed to determine the effect of education, which is based on health belief model, on the promotion of preventive behaviors for premenstrual syndrome among the female adolecents. Materials and Methods: This quasi-experimental study was conducted on 120 female adolecents assigned into the experimental and control groups (n=60 in each group). The study population was selected through multistage sampling method. Data collection was performed using a demographic form and a researcher-made questionnaire, enquiring the knowledge, behavior, and health belief model components. The educational intervention consisted of four lecture sessions of 45-60 min. The data were analyzed using the independent t-test, paired t-test, Mann-Whitney U, Wilcoxon, Kolmogorov-Smirnov, and Chi-square tests in SPSS software, version16. Results: Prior to the intervention, there was no significant difference between the experimental and control groups in terms of demographic and underlying characteristics, knowledge, preventive behaviors, and all components of the health belief model (P>0.05). However, a significant difference was observed between the two groups following the intervention regarding the mean score of knowledge, all components of health belief model, and preventive behaviors (P<0.001). Conclusion: The implementation of education based on the health belief model was effective in the adoption of preventive behaviors for premenstrual behavior. Given the importance of the female adolecents' health as future mothers and the low cost of health education activities, it seems necessary to develop these programs.